Transforming American governance : rebooting the public square - Balutis, Alan P.; Buss, Terry F.; Ink, Dwight, 1922- (Transformational trends in governance & democracy., 2011)
Natural disasters, terrorist attacks, ongoing wars, and global financial crises are forcing unprecedented changes in the institutions of government and public management. Government and governance will be very different in the future than anticipated in the literature in the field. Transforming American Governance is designed to help public management practitioners, thought leaders, theorists and researchers to ask the right questions as we move forward in this uncharted territory. The editors have assembled a prominent cast of experts to envision the future of government and governance on a b.